2019
DOI: 10.3389/fgene.2019.00777
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Long Noncoding RNAs and Their Responses to Salt Stress in Two Closely Related Poplars

Abstract: Long noncoding RNAs (lncRNAs) are involved in various biological regulatory processes, but their roles in plants resistance to salt stress remain largely unknown. To systematically explore the characteristics of lncRNAs and their roles in plant salt responses, we conducted strand-specific RNA-sequencing of four tissue types with salt treatments in two closely related poplars (Populus euphratica and Populus alba var. pyramidalis), and a total of 10,646 and 10,531 lncRNAs were identified, respectively. These lnc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 73 publications
1
26
0
Order By: Relevance
“…10). In poplar, more than 10,000 lncRNAs were identified, and approximately 40% of them responded to salt stress with tissue-specific expression patterns [34]. In cotton, lncRNA973 was localized in the nucleus and increased by salt treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10). In poplar, more than 10,000 lncRNAs were identified, and approximately 40% of them responded to salt stress with tissue-specific expression patterns [34]. In cotton, lncRNA973 was localized in the nucleus and increased by salt treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In rice, Ding et al found that the lncRNA long-day-specific malefertility-associated RNA is essential for the normal pollen development of plants grown under long-day conditions [30]. And also, more and more researches suggest that lncRNAs play important roles in the regulation of gene expression in response to various stresses [33][34][35][36][37][38]. An Arabidopsis lncRNA, DROUGHT IN-DUCED lncRNA (DRIR), was a new positive regulator of the plant response to drought and salt stress [37].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, there are no annotated and characterized oxidative stress-responsive cassava lncRNAs. However, there have been a few reports on lncRNAs involved in oxidative stress processes in plants such as Medicago, tobacco, and poplar [61][62][63].…”
Section: Functional Analysis Of Potential Novel Lncrnas Involved In Cmentioning
confidence: 99%
“…After exposure of Arabidopsis thaliana to drought, cold, high salt, or abscisic acid, the expression of 1832 lncRNAs was up-regulated markedly when compared with the control group [8]. More recently, genome-wide studies showed that lncRNAs respond to heat and salt stress in Chinese cabbage (Brassica rapa) and poplar (Populus trichocarpa), respectively [9,10].…”
Section: Introductionmentioning
confidence: 99%